Metasploit bootcamp a fast-paced guide to enhance your pentesting skills - Jaswal, Nipun (Packt Publishing, 2017)
A fast-paced guide that will quickly enhance your penetration testing skills in just 7 days. Carry out penetration testing in complex and highly-secured environments. Learn techniques to Integrate Metasploit with industry's leading tools.